Not with a bang but a whimper: Art that sprouts in a world in ruins - Souza, Alisson Ramos de; Balau, Luiza (Farol, 2024)
This article seeks to understand how art can position itself in the face of the new climate regime called the Anthropocene. To this end, works by two contemporary visual artists were chosen: Dan Lie and Denilson Baniwa. The reading of the works was carried out in conjunction with discussions of philosophy and anthropology, denouncing the complicity that exists between the notions of humanism, progress and predatory capitalism.